1995
DOI: 10.1007/bf00187172
|View full text |Cite
|
Sign up to set email alerts
|

New anastomosis technique for (laparoscopic) instrumental small-diameter anastomosis

Abstract: This study presents a new technique for visceral anastomosis. The principle consists of connecting the two parts to be anastomosed around a reabsorbable stent which is transluminally introduced into small-diameter viscus, where it is fixed. Advancing a larger tube along the axis of the machine, the larger, perforated viscus is inverted and pulled over the stent, and finally a rubber band pops off the machine endoluminally in order to fix the intestinal walls in seroserosal contact onto the stent. To evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The technique had been developed in an animal model at our institution [17,18]. It required the introduction of another subxyphoidal trocar (5-mm).…”
Section: Methodsmentioning
confidence: 99%
“…The technique had been developed in an animal model at our institution [17,18]. It required the introduction of another subxyphoidal trocar (5-mm).…”
Section: Methodsmentioning
confidence: 99%
“…The advent of laparoscopic surgery has added a new dimension to intraabdominal surgical procedures. It is now possible to perform complicated bowel surgery using newer laparoscopic instruments and techniques, including bowel anastomosis, 8,9 bowel bypass techniques 10 and closure of perforations and resection. 11 We report the results of 6 patients with typhoid peritonitis whom we managed successfully using minimally invasive methods.…”
mentioning
confidence: 99%
“…Detweiler et al [34][35][36] first reported successful cholecystojejunostomy in pigs using a combination of absorbable stents and fibrin glue. Using a similar technique via a laparoscopic approach, Schob et al 37,38 performed a hepaticojejunostomy using transient biofragmentable stents and intraluminal banding of the intestinal mucosa to temporarily secure the bowel to the transected bile duct (Figure 1). Most recently, Cai et al 39 reported an absorbable dual ring system for securing small-bowel serosa to the transected bile duct over an externalized stent.…”
mentioning
confidence: 99%
“…A. Cai et al39 : apposition of bile duct and jejunum secured with circumferential purse-string sutures (arrows) between 2 biofragmentable rings on an externalized catheter stent. B. Schob et al37,38 : bowel inverted over degradable bile duct stent and secured with circumferential band (arrows). C. Seal et al (present study, vide infra): anastomosis stabilized over a transhepatic cholangiocatheter and secured with an umbrella anchoring device circumferentially around and away from the anastomosis (arrows).…”
mentioning
confidence: 99%